Who Owns and Controls Farming Data? - Ziwen Yu; Albert De Vries; Yiannis Ampatzidis; D. Daniel Sokol (EDIS, 2021)
This publication aims to clarify the concerns regarding data ownership and explain the responsibilities of that ownership, sharing, and benefits in a collaborative smart farming application. Written by Ziwen Yu, Albert De Vries, Yiannis Ampatzidis, and D. Daniel Sokol, and published by the UF/IFAS Department of Agricultural and Biological Engineering, October 2021.